2019
DOI: 10.1371/journal.pone.0226177
|View full text |Cite
|
Sign up to set email alerts
|

Profusion of G-quadruplexes on both subunits of metazoan ribosomes

Abstract: Mammalian and bird ribosomes are nearly twice the mass of prokaryotic ribosomes in part because of their extraordinarily long rRNA tentacles. Human rRNA tentacles are not fully observable in current three-dimensional structures and their conformations remain to be fully resolved. In previous work we identified sequences that favor G-quadruplexes in silico and in vitro in rRNA tentacles of the human large ribosomal subunit. We demonstrated by experiment that these sequences form G-quadruplexes in vitro. Here, u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 37 publications
5
34
0
Order By: Relevance
“…Immunofluorescence experiments with BG4 and L19 antibodies suggest a specialized fraction of cytosolic ribosomes (~5%) form G4s and that most extra-nuclear G4s (~83%) are ribosomal. The small fraction of ribosomes observed to form G4s in vivo contrasts with the high stability of ribosomal G4s in vitro (7,8). This difference is consistent with Guo and Bartel, who propose that eukaryotic cells have a robust machinery that unfolds G4s (16).…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…Immunofluorescence experiments with BG4 and L19 antibodies suggest a specialized fraction of cytosolic ribosomes (~5%) form G4s and that most extra-nuclear G4s (~83%) are ribosomal. The small fraction of ribosomes observed to form G4s in vivo contrasts with the high stability of ribosomal G4s in vitro (7,8). This difference is consistent with Guo and Bartel, who propose that eukaryotic cells have a robust machinery that unfolds G4s (16).…”
Section: Discussionsupporting
confidence: 82%
“…We previously reported that surfaces of both the SSU and the LSU contain G4 sequences (7,8). A broad variety of data are consistent with more extensive formation of G4s on the LSU than on the SSU.…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations